1970
DOI: 10.1071/ar9700001
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis approach to selection of parents for hybridization aiming at yield improvement in self-pollinated crops

Abstract: A method of choosing parents for hybridization (aiming at yield improvement) by quantitatively measuring the genetic divergence is described, with the use of data on several characters measured on 40 genotypes of wheat (Triticum aestivum) which had their origin in different ecogeographic regions of Australia. The genotypes were grouped into 12 gene constellations by this method. The method of formulating a crossing programme based on the information on statistical distance between different gene constellations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
2

Year Published

1977
1977
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 0 publications
4
55
0
2
Order By: Relevance
“…Genetic diversity is a powerful tool to determine the genetic discrimination among the genotypes which is used to select appropriate parents for hybridization to develop high yielding variety (Bhatt, 1970). With the development of advanced biometrical techniques such as multivariate analysis based on the Mahalanobis (1936) statistics, quantification of divergence among the biological population and assessing the relative contribution of different components to the total divergence at intra and intercluster levels have now become possible.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity is a powerful tool to determine the genetic discrimination among the genotypes which is used to select appropriate parents for hybridization to develop high yielding variety (Bhatt, 1970). With the development of advanced biometrical techniques such as multivariate analysis based on the Mahalanobis (1936) statistics, quantification of divergence among the biological population and assessing the relative contribution of different components to the total divergence at intra and intercluster levels have now become possible.…”
Section: Introductionmentioning
confidence: 99%
“…Tomooka (1991) reported that evaluation of genetic diversity is important to know the source of gene for a particular trait within the available germplasm. Genetic diversity is a powerful tool to determine the genetic discrimination among the genotypes which is used to select appropriate plant genotypes for hybridization to develop high yielding potential variety (Bhatt, 1970). Biometrical techniques such as multivariate analysis based on the Mahalanobis (1936) statistics is used to quantify divergence among the biological population and assess the relative contribution of different components to the total divergence at intra and inter-cluster levels.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the clustering pattern shown in Figure 3 that the grouping of populations does not strictly represent the geographic origin, since very distant populations such as the grouping of the Tunisian population Nadour and the Moroccan population Morocco 008 were found to be associating with Italian populations. In other studies, it was also found that populations clustered in different groups irrespective of their countries of origin [2,4]. On the other hand, it has been determined that origin can be a simple means of partitioning variation in germplasm collections.…”
Section: Discussionmentioning
confidence: 93%